Force out - Green, Tim, 1963- (New York, NY : Harper, 2013)
"When Joey has to compete with his best friend, Zach, for a single spot on an elite baseball team, he is forced to decide how far he is willing to go to win"--
Ages 9-12.
Keywords: Baseball -- Fiction; Conduct of life -- Fiction; Competition (Psychology) -- Fiction; Best friends -- Fiction; Friendship -- Fiction; JUVENILE FICTION / Family / General (see also headings under Social Issues).; JUVENILE FICTION / Sports & Recreation / Baseball & Softball; JUVENILE FICTION / Social Issues / Adolescence